Comparative Evaluation of Compressive and Flexural Strengths of Two Resin-based Core Build-up Materials with an Alkasite Material: An In-vitro Approach - Vaithiyalingam, Abirami; Mathew, Miriam; Jayakumar, Srilekha; Arumugam, Karthikeyan; Ponnusamy, Prashanth; Narasimman, Thirupurasundari (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Aim: The present study compares and evaluates the compressive and flexural strengths of two resin-based core build-up materials with an alkasite material. Background: Several dental materials have been used for core build-up procedures, some as direct and some as indirect, such as a custom cast post and core. The material used for direct core build-up was not specifically developed for this purpose but found applications in core build-up due to properties such as fluoride release, adhesion to the tooth structure, choice of curing mechanism, and better handling properties to name a few. Materials and Methods: ParaCore®, Tetric® N-CeramTM Bulk-fill composite, and Cention N were used. A total of 90 specimens were prepared. Customized cylindrical split molds of dimension 6 \(±\) 1 mm (height) × 4 \(±\) 1 mm (diameter) were used to fabricate 15 samples of each core material for testing the compressive strength and rectangular split metal molds of dimensions 25 \(±\) 1 mm (length) × 2 \(±\) 1 mm (width) × 2 \(±\) 1 mm (height) were used to fabricate 15 samples of each core material for testing the flexural strength. Then the samples were tested using a Universal testing machine (UTM). Data were analyzed using a statistical package for social sciences (SPSS) version 22.0 (SPSS Inc, Chicago IL). Mean values of the experimental groups were compared using one-way ANOVA (Analysis of variance) and intergroup comparisons were made based on Post hoc values from Tukey’s test, at a 5% level of significance (p \(\le\) 0.05). Results: The compressive and flexural strengths of Cention N were significantly less than ParaCore® but higher than Tetric® N-CeramTM Bulk-fill core build-up material. The estimated p value for compressive strength was p = 0.013 and for flexural strength was p = 0.004. Compressive and flexural strength, Cention N exhibits lower microleakage, prevents the recurrence of caries (due to long-term release of fluoride, calcium, and hydroxyl ions), has proximal contact tightness, has a dual cure mechanism and possesses superior micro-hardness and fracture resistance properties. Conclusion: Within the limitations of this study, it was concluded that Cention N can be used as an alternative to other core build-up materials. Clinical Significance: Cention N had the added advantage that self-cure polymerization alone was sufficient to achieve good physical properties when compared to the other two resin-based core build-up materials.